Transcriptome Analysis of Rainbow Trout (Oncorhynchus mykiss) Eggs Subjected to the High Hydrostatic Pressure Treatment - Artur Gurgul; Klaudia Pawlina-Tyszko; Monika Bugno-Poniewierska; Tomasz Szmatoła; Igor Jasielczuk; Stefan Dobosz; Konrad Ocalewicz (International Journal of Genomics)
High hydrostatic pressure (HHP) causes depolymerization of the spindle microtubules. HHP applied to fish eggs prevents extrusion of the second polar body and inhibits the first cell cleavage, and it is used to produce triploids and diploid gynogenetic and androgenetic individuals. HHP has been also found to affect biomolecules including nucleic acids, and it may be presumed that HHP administered to the rainbow trout (Oncorhynchus mykiss) eggs disturbs cytoplasmic maternal RNA indispensable for the early embryogenesis. To verify this assumption, quality and quantity of RNA extracted from the rainbow trout eggs subjected to the high hydrostatic pressure shock were analyzed. Provided results exhibited that maternal transcriptome was resistant to a three-minute exposure to 65.5 MPa of HHP treatment. Some trend showing increase of the RNA integrity was observed in the HHP-treated eggs; however, the difference was not statistically significant. Alterations in the expression profiles in the rainbow trout eggs subjected to HHP were also negligible. Greater differences in the maternal gene expression were observed between eggs from different clutches than between HHP-treated and untreated eggs from the same clutch. It may be assumed that exposure to HHP shock was too short to modify significantly maternal transcripts in the rainbow trout eggs.